Integral Sliding Mode Control of BLDC Motor considering Nonlinear Friction Model - Jang, Ji Young; Heo, Junseo; Chwa, Dongkyoung (Transactions of the Korean Institute of Electrical Engineers, 2022)
This paper proposes an integral sliding mode control method for robust control of brushless direct current (BLDC) motor. In order to improve the control performance, the friction force of the motor is expressed using the Stribeck friction model, which is a nonlinear friction model that can accurately represent the friction force at low speed. The parameter values required to design the integral sliding mode controller are then obtained by identifying the parameters of the dynamic equations of the motor including the nonlinear friction model using the Levenberg-Marquardt (LM) algorithm. The performance of the proposed integral sliding mode control method for the BLDC motor is verified through both the simulation results and the actual motor speed control test results.
Keywords: Brushless direct current motor; Control methods; Friction force; Friction modeling; Integral sliding mode; Integral sliding mode control; Integral sliding mode controller; Nonlinear friction; Sliding mode controller; Stribeck friction; friction force; Integral sliding mode controller; robust control; Stribeck friction